Integrated transcriptomic analysis reveals evolutionary and developmental characteristics of tendon ossification in teleost - Xu-Dong Wang; Fei-Long Shi; Jia-Jia Zhou; Zheng-Yu Xiao; Tan Tu; Xue-Mei Xiong; Chun-Hong Nie; Shi-Ming Wan; Ze-Xia Gao (BMC Biology)
Abstract Background Intermuscular bones (IBs) are segmental intramembranous ossifications located within myosepta. They share similarities with tendon ossification, a form of heterotopic ossification (HO). The mechanisms underlying IB formation remain incompletely understood. Results In this study, we systematically analyzed transcriptome data across multiple tissues, species, time points, and resolutions in teleosts. First, we identified IB-specific expression genes using the tau index method. Through cross-species comparisons of the tendon development process, we discovered that candidate genes were primarily enriched in extracellular matrix organization, ossification, regulation of angiogenesis, and other related processes. We also revealed that some of these candidate genes are abnormally expressed in runx2b −/− zebrafish, which lack IBs. To clarify the trajectory of cell differentiation during IB formation, we demonstrated that myoseptal stem cells differentiate into osteoblasts, fibroblasts, and tenocytes in runx2b +/+ zebrafish. However, in runx2b −/− zebrafish, the differentiation of myoseptal stem cell into osteoblast was inhibited, while differentiation into clec3bb + tenocyte and fibroblast was enhanced. Additionally, runx2b deficiency led to the upregulation of clec3bb expression in the clec3bb + tenocyte cluster. Notably, a compensatory effect was observed in cell differentiation and gene expression in runx2b −/− zebrafish, suggesting that runx2b and the candidate genes, such as clec3bb, were involved in the gene network of IB development. Conclusions The results elucidate cell differentiation process during tendon ossification in teleosts and identify the key factor clec3bb involved in this process. These findings provide a foundation for understanding tendon ossification in teleosts and for further research on tendon ossification in mammals.